ISSUES OF ATTRACTING FOREIGN INVESTMENTS TO THE REGIONS OF UZBEKISTAN: PROBLEMS AND SOLUTIONS - Sh.S. Oltaev (INTERNATIONAL JOURNAL OF SOCIAL SCIENCE & INTERDISCIPLINARY RESEARCH ISSN: 2277-3630 Impact factor: 8.036, 2022)
This article covers the investment potential of the regions of the Republic of Uzbekistan, the role of investments in the economic and social development of the regions, and the issues of attracting foreign investments to the regions of the country. The index of investment attractiveness of regions, the analysis of foreign investments attracted to the regions of our country in recent years, and the ways of attracting investments to regions and increasing their efficiency are presented.